2012
DOI: 10.3109/08880018.2012.700387
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Retinoblastoma with Four-Drug Regimen Including Cisplatin, Etoposide, Vincristine, and Cyclophosphamide

Abstract: Over an 11-year period, 59 patients (83 eyes) were treated with four-drug chemotherapy (cisplatin, etoposide, cyclophosphamide, and vincristine) at Hacettepe University, Departments of Ophthalmology and Pediatric Oncology. We evaluated the clinical features, treatment modalities, and outcome of these patients with a median follow-up of 55 months (range 9-130 months). Enucleation was performed as a first-line treatment for 30 eyes due to iris neovascularization and neovascular glaucoma, tumor in the anterior ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Shields et al [4] reported that the ICRB can predict the success of chemoreduction. The conventional treatment options are systemic chemotherapy, local therapy (i.e., cryotherapy, thermotherapy, laser photocoagulation and plaque radiotherapy), external beam radiotherapy and enucleation [5]. Long-term control can be achieved with carboplatin, etoposide and vincristine treatment when used in combination with local therapies [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shields et al [4] reported that the ICRB can predict the success of chemoreduction. The conventional treatment options are systemic chemotherapy, local therapy (i.e., cryotherapy, thermotherapy, laser photocoagulation and plaque radiotherapy), external beam radiotherapy and enucleation [5]. Long-term control can be achieved with carboplatin, etoposide and vincristine treatment when used in combination with local therapies [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment success is not satisfactory in the advanced stage of the disease, particularly for those with vitreous seeding. Systemic chemotherapy results in side effects, such as myelosuppression, ototoxicity, failure to thrive, as well as nephrotoxicity [5]. Focal therapy has a limited effect in the advanced stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Searching for novel prognostic markers of RB, therefore, remains urgent for us. Most RB cases are diagnosed at an advanced stage before the age of 5, which accounts for the high mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During the past years, different treatments such as enucleation, externalbeam radiotherapy and chemotherapy were developed, but the overall survival rate remains far from favorable due to limited early diagnosis. 3,4 Searching for novel prognostic markers of RB, therefore, remains urgent for us. S-phase kinase-associated protein 2 (SKP2), which is also called FBXL1 or p45, belongs to the F-box protein family.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoblastoma (RB) is a rare type of eye cancer that usually develops in childhood, with an average incidence of one case for every 15,000–20,000 live births . Treatment and diagnostic modalities associated with this disease are changing rapidly according to our understanding . RB was traditionally treated with enucleation and external‐beam radiotherapy; however, in the past decade, systemic chemotherapy has become the primary globe‐salvaging approach .…”
Section: Introductionmentioning
confidence: 99%